Genetic infrapopulation sizes in blood parasites: a pilot quantification of the bottleneck in louse fly vectors - Fischer, Kai; Chakarov, Nayden (Frontiers in Ecology and Evolution, 2024)
Bottleneck events are crucial for the strength of genetic drift, selection and speed of evolution. They are believed to play a particularly prominent role for parasitic infrapopulations, inhabiting single host individuals, which are often established by very few parasite individuals during transmission. In vectorborne pathogens, the bottlenecking effects can even be serialized through repeated filtering of parasitic stages at different tissues and organs of the vector. Using qPCR we aimed to quantify the number of potentially transmittable sporozoites of the haemosporidian blood parasite Haemoproteus columbae in the specialized vector louse flies Pseudolynchia canariensis which transmit these parasites between house pigeon hosts Columba livia. Based on qPCR measurements of organ-derived DNA of individual louse flies, we estimate that the midgut of these vectors contains on average 20 parasites, the hindgut and other intestines ca. 50 parasites and the salivary glands ca. 5 parasite cells. Nearly one third of all vector individuals appeared to lack parasite DNA, despite having only infected hosts as blood meal sources. The magnitude of parasite numbers in midgut and salivary glands tended to correlate positively. Our results indicate, potential severe bottlenecking of parasite populations during individual transmission events and a probable effect of individual vector immunity on this variable. However, this may be partly alleviated by the coloniality of house pigeons, the frequency of louse flies and their daily feeding events in most populations, leading to repeated transmission opportunities, decreased quasivertical transmission between parents and offspring and probable panmixia of Haemoproteus columbae lineages. Many of these mechanisms might not apply in other host-vector systems. We propose several additional molecular and microscopical tools to improve the accuracy of estimating parasite population sizes in vectors and call for more estimations in different vector species to better understand the co-evolution between malaria-like blood parasites and their avian and insect hosts.